A Novel Sesquiterpene Lactone Xanthatin-13-(pyrrolidine-2-carboxylic acid) Isolated from Burdock Leaf Up-Regulates Cells' Oxidative Stress Defense Pathway - Yanis A. Idres; Didier Tousch; Guillaume Cazals; Aurélien Lebrun; Sarah Naceri; Luc P. R. Bidel; Patrick Poucheret (MDPI AG, 2021)
The aim of our study was to identify novel molecules able to induce an adaptative response against oxidative stress during the first stages of metabolic syndrome. A cellular survival in vitro test against H2O2-based test was applied after pretreatment with various natural bitter Asteraceae extracts. This screening revealed potent protection from burdock leaf extract. Using chromatography and LC-MS-RMN, we then isolated and identified an original sesquiterpene lactone bioactive molecule: the Xanthatin-13-(pyrrolidine-2-carboxylic acid) (XPc). A real-time RT-qPCR experiment was carried out on three essential genes involved in oxidative stress protection: GPx, SOD, and G6PD. In presence of XPc, an over-expression of the G6PD gene was recorded, whereas no modification of the two others genes could be observed. A biochemical docking approach demonstrated that XPc had a high probability to directly interact with G6PD at different positions. One of the most probable docking sites corresponds precisely to the binding site of AG1, known to stabilize the G6PD dimeric form and enhance its activity. In conclusion, this novel sesquiterpene lactone XPc might be a promising prophylactic bioactive agent against oxidative stress and inflammation in chronic diseases such as metabolic syndrome or type 2 diabetes.